PENGARUH INFLASI, SUKU BUNGA, LIKUIDITAS, DAN BAGI HASIL TERHADAP DEPOSITO MUDHARABAH - Farizi, Fauzan Al; Riduwan, Akhmad (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to test the influence of inflation rates, interest rates, liquidity rates which are proxy by the finance to deposit ratio and profit sharing rates to the amount of mudharabah deposit at Bank Rakyat Indonesia Syariah in 2010 â 2014. This research applies quantitative method. The data has been done by using secondary data and time series which have been retrieved from the financial statement of Bank Rakyat Indonesia Syariah and the Financial Statistic of Bank Indonesia. The sample uses quarterly financial statement from 2010 to 2014. The regressions analysis has been done by using significance test of the influence of inflation rates, interest rates, liquidity rates which are proxy by the finance to deposit ratio and profit sharing rates partially to the mudharabah deposit. The result of this research gives prove that: (a) inflation rates does not have any influence to the amount of deposit mudharabah; (b) the interest rates has positive significant to the amount of deposit mudharabah of Bank Rakyat Indonesia Syariah because when the interest of conventional bank increase, the amount of deposit mudharabah do not experience dramatic changes because the customers still invest their fund at Bank Rakyat Indonesia Syariah; (c) finance to deposit ratio does not have any influence to the amount of mudharabah deposit; and (d) the rates of share profit does not have any influence to the amount of mudharabah deposit. Keywords: mudharabah deposit, inflations rates, interest rates, finance to deposit ratio, profit sharing rates.